India's power struggles. - Singh, V.
In this paper the authors detail how Indian infrastructure and management problems are slowing down the much-needed power sector reforms and clean-power initiatives that are still in their early stages
Keywords: India; Clean-power initiatives; Electric power industry; Infrastructure; Management problems; Power sector reforms